Clinical and genetic analysis of Christianson syndrome caused by variant of SLC9A6: case report and literature review - Dong, Yan; Lian, Ruofei; Jin, Liang; Zhao, Shichao; Tao, Wenpeng; Wang, Lijun; Li, Mengchun; Jia, Tianming; Chen, Xuejing; Cao, Shushi (Frontiers in Neurology, 2023)
Background Intellectual disability, X-linked, syndromic, Christianson type (MRXSCH, OMIM: 300243)—known as Christianson syndrome (CS)—is characterized by microcephaly, epilepsy, ataxia, and absence of verbal language ability. CS is attributed to mutations in the solute carrier family 9 member A6 gene (SLC9A6). Materials and methods This study reports the case of a boy 1 year and 3 months of age who was diagnosed with CS in our department. Genetic etiology was determined by whole-exome sequencing, and a minigene splicing assay was used to verify whether the mutation affected splicing. A literature review of CS cases was conducted and the clinical and genetic features were summarized. Results The main clinical manifestations of CS include seizures, developmental regression, and exceptional facial features. Whole-exome sequencing revealed a de novo splice variant in intron 11 (c.1366 + 1G > C) of SLC9A6. The mutation produced two abnormal mRNA products (verified by a minigene splicing assay), resulting in the formation of truncated protein. A total of 95 CS cases were identified in the literature, with various symptoms, such as delayed intellectual development (95/95, 100.00%), epilepsy (87/88, 98.86%), and absent verbal language (75/83, 90.36%). At least 50 pathogenic variants of SLC9A6 have been identified, with the highest frequency observed in exon 12. Conclusion Our patient is the first case with the c.1366 + 1G > C variant of SLC9A6 in CS. The summary of known cases can serve as a reference for analyzing the mutation spectrum and pathogenesis of CS.